2014
DOI: 10.1108/ccm-10-2012-0103
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring relationships among managerial and professional women in Turkey

Abstract: Purpose – Although qualified women are still underrepresented at ranks of senior management in all countries, considerable progress has been made in identifying work experiences associated with career success and advancement. The studies of mentor relationships in North America have shown that women receiving more functions from their mentors reported benefits such as greater job and career satisfaction, and female mentors provided more psychosocial functions than did male mentors. The present study examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Academic literature supports these empirical findings with Koyuncu, Burke, Alayoglu and Wolpin (2014) acknowledging that whilst significant progress has been made in understanding the barriers facing women in career advancement, they continue to be in the minority in more senior management roles internationally. Cross (2010) …”
Section: Women In the Labour Marketmentioning
confidence: 54%
“…Academic literature supports these empirical findings with Koyuncu, Burke, Alayoglu and Wolpin (2014) acknowledging that whilst significant progress has been made in understanding the barriers facing women in career advancement, they continue to be in the minority in more senior management roles internationally. Cross (2010) …”
Section: Women In the Labour Marketmentioning
confidence: 54%
“…Academic literature supports these empirical findings with Koyuncu, Burke, Alayoglu and Wolpin (2014) acknowledging that whilst significant progress has been made in understanding the barriers facing women in career advancement, they continue to be in the minority in more senior management roles internationally. Cross (2010) Garavan Hogan and Cahir-O'Donnell (2009) within an Irish and UK context specifically, identified that women "have suffered a degree of ghettoization in their managerial roles" (p. 74).…”
Section: Women In the Labour Marketmentioning
confidence: 54%
“…The sample consisted predominantly of women 14 . It is a common feature of the healthcare sector in Turkey where more women than men are involved in 14 Even though there is a fact that society still has a perception claiming women are not suitable for corporate culture (Koyuncu, M., Burke, R. J., Alayoglu, N., & Wolpin, J. (2014).…”
Section: Samplementioning
confidence: 99%